The Role of the Motivation in Changes and Performance Assessment of the Managerial Staff in Kosovo Businesses - Karaxha, Hidajet; Karaxha, Halit; Ramosaj, Berim (European Scientific Journal, ESJ, 2018)
Performance evaluation functions as an important tool in adjusting performance potential by removing intermediate barriers and motivating human resources. Each business objectives relate to performance motivation, helping individuals to improve their skills, creating a performance culture, determining which should be promoted, and eliminating employees who have low performance. The paper deals with the moderating role of performance evaluation in motivating managers in Kosovo businesses. This paper consists of the use of a methodology that incorporates a combination of primary and secondary data. The majority of secondary data includes research relevant literature from different libraries, the latest scientific research. Primary data constitute field findings from businesses interviewed in Kosovo. In this study, quantitative approach was used. This approach consists of data collection and analysis in various forms. In order to determine the impact of performance evaluation on motivation of managerial staff, a questionnaire was drafted. This questionnaire was addressed to owners/co-owners, directors, general directors, and all managers in Kosovo’s businesses. The last part of this paper is related to discussion of results, conclusions, and recommendations.